Pengaruh Senam Kegel terhadap Frekuensi Buang Air Kecil pada Ibu Hamil Trimester III - Abuba, Sartika; Nikmathul Husna Ali, Rizky; Yunus, Yuliandary; Nur Octaviani Katili, Dwi (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Complaints of frequent urination during the third trimester can cause discomfort for pregnant women. Physically, this condition can disrupt the mother's activity patterns, as the increased frequency of urination can hinder daily activities and disturb rest patterns. Kegel exercises, aimed at strengthening the bladder sphincter and pelvic floor muscles, were one method that could help reduce the frequency of urination in pregnant women. The purpose of this study was to determine the effect of Kegel exercises on urination frequency in pregnant women during their third trimester. This research was conducted as a quasi-experimental study with a nonequivalent group design, using the Wilcoxon statistical test. Sampling was performed through purposive sampling, with 15 participants in the intervention group and 15 in the control group. The results showed that, in the intervention group, the pre-test frequency of urination categorized as frequent was recorded for nine pregnant women. After the post-test, there was a change in urination frequency, with 12 pregnant women now categorized as infrequent. Meanwhile, in the control group, the pre-test frequency of urination categorized as frequent was recorded for four pregnant women. After the post-test, there was an increase, with 12 pregnant women still categorized as frequent. There was a significant effect of Kegel exercises on urination frequency in pregnant women during their third trimester, with a p-value of 0.001 < 0.05. In conclusion, Kegel exercises affected the frequency of urination in pregnant women during their third trimester at the Bongomeme Health Center.